Expression of UDP‐glucuronosyltransferase 1A in bladder cancer: Association with prognosis and regulation by estrogen. Issue 4 (9th November 2012) - Izumi, Koji; Li, Yi; Ishiguro, Hitoshi; Zheng, Yichun; Yao, Jorge L.; Netto, George J.; Miyamoto, Hiroshi
Abstract Although UDP‐glucuronosyltransferase 1A (UGT1A) plays an important role in preventing bladder cancer initiation by detoxifying carcinogenic compounds, its contribution to bladder cancer progression is poorly understood. We immunohistochemically stained for UGT1A in bladder specimens. UGT1A was positive in 130/145 (90%; 28 [19%] weak, 53 [37%] moderate, and 49 [34%] strong) urothelial neoplasms, which was significantly weaker than in matched non‐neoplastic urothelial tissues (100/101 [99%]; 2 [2%] weak, 17 [17%] moderate, and 81 [80%] strong). Fifty (98%) of 51 low‐grade/79 (99%) of 80 non‐muscle‐invasive tumors were immunoreactive to UGT1A, whereas 80 (85%) of 94 high‐grade/51 (78%) of 65 muscle‐invasive tumors were UGT1A‐positive. Kaplan‐Meier analysis showed strong associations between lower UGT1A expression versus the risk of recurrence in high‐grade non‐muscle‐invasive tumors (P = 0.038) or disease‐specific mortality in muscle‐invasive tumors (P = 0.016). Multivariate analysis further revealed UGT1A loss as an independent prognosticator for disease‐specific mortality in patients with muscle‐invasive tumor (P = 0.010). Additionally, the expression of UGT1A was positively and negatively correlated with those of estrogen receptor‐α and estrogen receptor‐β, respectively. We then assessed UGT1A/Ugt1a levels in human cell lines/mouse tissues. 17β‐Estradiol increased and decreased UGT1A expression in normal urothelium and bladder cancer lines, respectively, and an anti‐estrogen abolished these effects. Ovariectomy in mice resulted in down‐regulation of Ugt1a subtypes. These results suggest the involvement of UGT1A in not only bladder carcinogenesis but tumor progression. Moreover, UGT1A is likely regulated by estrogens in non‐neoplastic urothelium versus bladder tumor in opposite manners, which could be underlying mechanisms of gender‐specific differences in bladder cancer incidence and progression. © 2012 Wiley Periodicals, Inc.